Developing a selection scheme for dual virtual-metrology outputs - Wei-Ming Wu; Fan-Tien Cheng; Deng-Lin Zeng; Tung-Ho Lin; Jyun-fang Chen (2008 IEEE International Conference on Automation Science and Engineering, 2008)
This paper proposes a selection scheme (S-scheme) between neural-network (NN) and multiple-regression (MR) outputs of a virtual metrology system (VMS). Both NN and MR are applicable algorithms for implementing VM conjecture models. But a MR algorithm may achieve better accuracy only with a stable process, whereas a NN algorithm may has superior accuracy when equipment property drift or shift occurs. To take advantage of the merits of both MR and NN algorithms, the S-scheme is proposed to enhance virtual-metrology (VM) conjecture accuracy. Two illustrative examples in the CVD process of fifth generation TFT-LCD are used to test and compare the conjecture accuracy among solo NN, solo MR, and S-scheme. One-hidden-layered back-propagation neural network (BPNN-I) is adopted for establishing the NN conjecture model. Test results show that the conjecture accuracy of S-scheme can achieve superior accuracy than solo NN and solo MR algorithms.